DISIPLIN KERJA DALAM MENINGKATKAN KINERJA TENAGA PENDIDIK DAN KEPENDIDIKAN DI PONDOK PESANTREN SE-KECAMATAN BENGKALIS - Robi’ah Robi’ah; Iwan Agus Supriono (Program Studi PAI STAI Al Falah Banjarbaru, 2019)
The discipline of Islamic boarding schools is part of the organizational component as recommended in Islam, which is just like timeliness and is prohibited from delaying work. A good organization is an organization that can realize its goals effectively and efficiently with high productivity. The purpose of the organization will be achieved if the established work programs can be implemented effectively and efficiently. For the sake of carrying out the predetermined work program. This research was conducted in Islamic boarding schools in Bengkalis District and used descriptive methods. The data collection technique used is through observation, interviews, and documentation. The data analysis technique is triangulation. The results of the study show that the work discipline of Islamic boarding schools in Bengkalis District is good and can improve the performance of educators and education staff. The work discipline of educators and education Staff is relatively effective so that indiscipline actions can be reduced relatively small, because there is guidance from the leadership of the foundation carried out with kinship and openness, in finding solutions needed by educators and education staff. Keywords: Work discipline, Performance